Impact of robotics within Scratch block-based visual programming on computational thinking in primary school students (Journal of Educational Sciences, 2023)
This paper examines the impact of a robotics course using the Scratch 3.0 tool on the computational thinking of elementary school students. The study was conducted at the KSU «IT school-lyceum № 28 named after Kuljabai Kasymov» in Kazakhstan among 48 third-graders with basic programming skills, divided into a control group and an experimental one. Prior to the experiment, all participants were asked to create a robot in Scratch 3.0. The students in the experimental group attended robotics classes for two weeks, while the participants in the control group followed conventional curriculum. Upon completion of the course, participants in both groups were tasked with creating a game. The students' projects before and after the experiment were scored using the Dr. Scratch platform. The data were analyzed using descriptive statistics to obtain group averages and standard deviations. In order to examine the effect of using the Scratch 3.0 tool on students' computational thinking, an independent two-tailed t-test was performed to estimate the size of between-group differences. Post-test computational thinking scores of the students who completed practical tasks on Scratch were significantly higher by 31.8% compared to their peers who attended regular classes (P